Scaffolding Based on Telolet Game in Teaching Integers - Wulandari, Yunita Oktavia; Damayanti, Nia Wahyu (Universitas Malikussaleh, Aceh Utara, Indonesia, 2018)
Scaffolding is defined as help that can assist students to solve problems or understand concepts that were not able to complete independently. In modern times, the concept of technology-based Scaffolding in learning has developed. In this study an educational game called